Electrochemical analysis of the performance loss in all vanadium redox flow batteries using different cut-off voltages. (10th January 2017) - Derr, Igor; Fetyan, Abdulmonem; Schutjajew, Konstantin; Roth, Christina
Abstract: The performance loss observed in vanadium redox flow batteries over time strongly depends on the material and the cycling conditions. We have chosen 1.65 V and 1.8 V as the cut-off voltages in order to compare the performance loss and the risk of evolving hydrogen on the negative side and CO2 on the positive side. The 1.8 V experiment was expected to show stronger degradation because of the higher risk of hydrogen and CO2 evolution due to the higher maximum half-cell potentials. To address this issue we implemented a reference electrode at the inlet of the negative half-cell of a 10 cm 2 test cell. The discharge process on the negative half-cell was assumed to be the process with the highest overpotential after running 50 charge and discharge cycles. After 50 cycles the reduction of V(II) remained the favored reaction compared to the HER in the negative side, even though the overpotentials for both reactions increased significantly. As for the positive half-cell, the risk of CO2 evolution increased with increasing cut-off voltage. The higher cut-off voltage led to a higher rate of degradation, but it also showed a better overall performance. The potentials in the half-cells were changing dynamically with each cycle depending on the degradation rate of the electrode and the state of the electrolyte. An imbalance of the electrolyte could be observed by measuring the half-cell open circuit potential after each charge and discharge process. The obtained results can be used for the diagnostics and optimization of VRFB systems in order to achieve maximum system output at reasonable risks of parasitic reactions and degradation.